Crystal structure of 5,11,17,23-tetrabromo-25,27-dihydroxy- 26,28-dimethoxycalix[4]arene, C30H24Br4O4 - Luo Y.-H.; Hu X.-J.; Liu J.-K.; Zhang H.; Li Y.; Yang H.-J.; Wang R.-J. (Zeitschrift für Kristallographie - New Crystal Structures, 2006)
C30H24Br4O4, monoclinic, P121/c1 (no. 14), a = 9.810(1) Å, b = 27.121(6) Å, c = 11.410(3) Å, β = 110.31(1)°, V = 2846.9 Å3, Z = 4, Rgt(F) = 0.068, wRref(F2) = 0.126, T = 295 K.